In Vitro Activities of 2,4-Diaminoquinazoline and 2,4-Diaminopteridine Derivatives against Plasmodium falciparum - Ommeh, Sheila (American Society for Microbiology, 2004)
The activities of 28 6-substituted 2,4-diaminoquinazolines, 2,4-diamino-5,6,7,8-tetrahydroquinazolines, and 2,4-diaminopteridines against Plasmodium falciparum were tested. The 50% inhibitory concentrations (IC(50)s) of six compounds were <50 nM, and the most potent compound was 2,4-diamino-5-chloro-6-[N-(2,5-dimethoxybenzyl)amino]quinazoline (compound 1), with an IC(50) of 9 nM. The activity of compound 1 was potentiated by the dihydropteroate synthase inhibitor dapsone, an indication that these compounds are inhibitors of dihydrofolate reductase. Further studies are warranted to assess the therapeutic potential of this combination in vivo.